Avatar Therapy for persistent auditory verbal hallucinations: a case report of a peer research assistant on his path toward recovery. Issue 3 (3rd July 2018) - Dellazizzo, Laura; Percie du Sert, Olivier; Potvin, Stéphane; Breton, Richard; Pelletier, Jean-François; Renaud, Patrice; Dumais, Alexandre
ABSTRACT: Peer support promotes the overall wellness of people with mental illness by establishing mutual partnerships throughout their different stages of recovery. In health research, investments in patient-oriented research have become prioritized. However, peer-contributed research remains relatively rare, especially in the study of psychosis. Our research team chose to include a peer research assistant in the elaboration and refinement of a novel personalized and patient-oriented psychotherapy for voice hearers, using virtual reality (Avatar Therapy (AT)). This paper details the case of a partnership between a mental health service user and clinical researchers by showcasing Mr X, the first to follow the therapy for his input and our peer support worker for future patients, in his journey toward recovery. Before AT, Mr X was unable to advance due to his voices. His participation was to initially gain from his personal expertise and invite his critique to improve AT. However, what he gained from AT was much more; his voices diminished by 80–90% and he was able to reduce his medication on four occasions. Also, he followed a university-level peer helper program and became employed. Mr X is an inspirational case of how AT may have a positive impact on one's life.